2007
DOI: 10.1177/155892500700200303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fibers Produced from Blends of Polybutylene and Polypropylene

Abstract: Other crystalline polymer pairs have been studied wherein a synergism was found in their mechanical properties. For example, PP/HDPE was studied by Noel and Carley (1975) in a wide range of compositions. They found that very low amounts of HDPE caused a maximum in the tensile modulus and strength of the blends. They concluded that, when the HDPE component is less than 10%, the HDPE acts as a stiffener. In contrast, small amounts of PP were found to make the blend ductile. Stell et al. (1976) studied polymer bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…When blended with PB-1, PP actively accelerates the crystal transition of PB-1 [5] . Shambaugh et al [6] studied the characterization of fibers produced by blends of PB-1 and PP. Their group reported that these fibers exhibit mechanical properties that fall in between the values of the two pure polymers.…”
Section: Introductionmentioning
confidence: 99%
“…When blended with PB-1, PP actively accelerates the crystal transition of PB-1 [5] . Shambaugh et al [6] studied the characterization of fibers produced by blends of PB-1 and PP. Their group reported that these fibers exhibit mechanical properties that fall in between the values of the two pure polymers.…”
Section: Introductionmentioning
confidence: 99%